Lower Limb Muscle Strength and Muscle Mass Are Associated With Incident Symptomatic Knee Osteoarthritis: A Longitudinal Cohort Study - Veronese, Nicola; Stefanac, Sinisa; Koyanagi, Ai; Al-Daghri, Nasser M.; Sabico, Shaun; Cooper, Cyrus; Rizzoli, Renè; Reginster, Jean-Yves; Barbagallo, Mario; Dominguez, Ligia J.; Smith, Lee; Maggi, Stefania (Frontiers in Endocrinology, 2021)
Recent literature suggests that sarcopenia, often represented by low lower limbs muscle mass and strength, can be considered a potential risk factor for knee osteoarthritis (OA), but the available literature is still limited. We therefore aimed to investigate whether sarcopenia is associated with a higher risk of radiographic (ROA) and symptomatic knee OA (SxOA) in a large cohort of North American people in the context of the OA initiative. Sarcopenia at baseline was diagnosed in case of low skeletal muscle mass (i.e., lower skeletal mass index) and poor performance in the chair stands test. The outcomes of interest for this study included ROA (radiographical osteoarthritis) if a knee developed a Kellgren and Lawrence (KL) grade ≥2 at follow-up, and SxOA (symptomatic osteoarthritis) defined as new onset of a combination of painful knee OA. Altogether, 2,492 older participants (mean age: 68.4 years, 61.4% females) were included. At baseline, sarcopenia was present in 6.1% of the population. No significant difference in ROA prevalence was observed between those with and without sarcopenia (p=0.76), whilst people with sarcopenia reported a significant higher prevalence of SxOA (p<0.0001). Using a logistic regression analysis, adjusting for potential confounders at baseline and the diagnosis of sarcopenia during follow-up, sarcopenia was associated with a higher incidence of knee SxOA (odds ratio, OR=2.29; 95%CI [confidence interval]: 1.42-3.71; p=0.001), but not knee ROA (OR=1.48; 95%CI: 0.53-4.10; p=0.45). In conclusion, sarcopenia could be associated with a higher risk of negative knee OA outcomes, in particular symptomatic forms.